2017
DOI: 10.1021/acs.chemrev.6b00695
|View full text |Cite
|
Sign up to set email alerts
|

Smart N-Heterocyclic Carbene Ligands in Catalysis

Abstract: It is well-recognized that N-heterocyclic carbene (NHC) ligands have provided a new dimension to the design of homogeneous catalysts. Part of the success of this type of ligands resides in the limitless access to a variety of topologies with tuned electronic properties, but also in the ability of a family of NHCs that are able to adapt their properties to the specific requirements of individual catalytic transformations. The term "smart" is used here to refer to switchable, multifunctional, adaptable, or tunab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
458
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 837 publications
(490 citation statements)
references
References 321 publications
6
458
0
4
Order By: Relevance
“…Usually, carbon uses all of its four valence electrons to form stable tetravalent carbon(IV) species. Since the first stable singlet carbene at room temperature was isolated by Bertrand and coworkers 3 , divalent carbon(II) chemistry, such as N-heterocyclic carbene (NHC) 69 and cyclic (alkyl)(amino)carbenes 1013 , has flourished. Carbenes, CR 2 , which contain one lone electron pair, can coordinate to numerous main group atoms and d -block or even f -block elements forming stable species via a single dative bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, carbon uses all of its four valence electrons to form stable tetravalent carbon(IV) species. Since the first stable singlet carbene at room temperature was isolated by Bertrand and coworkers 3 , divalent carbon(II) chemistry, such as N-heterocyclic carbene (NHC) 69 and cyclic (alkyl)(amino)carbenes 1013 , has flourished. Carbenes, CR 2 , which contain one lone electron pair, can coordinate to numerous main group atoms and d -block or even f -block elements forming stable species via a single dative bond.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fundamental difference between a carbene CR 2 and a carbone CL 2 is the number of electron lone-pairs that may serve as donors: carbenes are two-electron (single lone-pair) donors while carbones are four-electron (double lone-pair) donors. Although the first divalent carbon(0) species 9 , carbodiphosphorane (CDP), was reported already in 1961, the actual bonding situation was not fully understood until a theoretical study appeared in 2006 by Frenking and coworkers 2729 . They showed that CDP can be considered as two phosphine ligands coordinated to a carbon atom in the excited 1 D state with two lone electron pairs, which remain available for both σ- and π-donation simultaneously 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As an interesting application, ferrocene‐based NHCs can be used as redox‐active ligands by changing the oxidation state of the Fe center . In a study to examine the redox chemistry of Rh complex 63 , which contains an achiral ferrocenyl phosphine‐NHC ligand, Labande and co‐workers reported in 2013 that they accidentally obtained planar‐chiral Rh complex 64 , which was probably formed by an intramolecular C−H activation of a ferrocene C−H bond on Rh triggered by oxidation of the Fe center (Scheme ) .…”
Section: Other Types Of Ligandmentioning
confidence: 99%
“…These facts have led to the development of a wide range of catalytic applications with metal−NHC complexes over recent decades. Along this line, NHC complexes of palladium have been widely considered to be used in Pd‐catalyzed reactions such as carbon–carbon and carbon−heteroatom coupling reactions due to the high performance and efficiency of these catalyst systems . Because both NHC ligands and Pd metal are valuable, the recycling and reuse of Pd−NHC catalysts is challenging.…”
Section: Introductionmentioning
confidence: 99%